Assess the Caregiver’s Knowledge on the Adverse Effect of Antipsychotics in the Selected Psychiatric unit of South India - Joyce Fernandes1 , Sukesh Shetty2 , Nalini.M3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background of the study: Antipsychotic drugs are chemicals that influence the brain and nervous systemin various ways, and they are frequently used in the practice of psychiatry to treat a broad range of mentaland emotional illness. The use of antipsychotics has reduced the number of patients hospitalized for mentalillness up to 50 % in the United States. Researchers worldwide have compared various family interventionsto enhance caregiver’s knowledge of antipsychotics, its side effects and prevent relapse, which concludedthat Psycho educational interventions are more effective in increasing knowledge and reducing stress amongthe caregivers. Psycho educational intervention is a systematic approach based on patients and family needs.The psycho education mainly emphasizes improving patient and family knowledge about the disease,coping with illness, and managing the adverse drug effects of psychotic drugs. The study aimed to assess thecaregiver’s level of knowledge on the adverse effects of antipsychotics and its association with the selecteddemographic variablesMethods: A descriptive survey design was used in this study with the one hundred study participantsselected using a purposive sampling technique and visiting the tertiary hospital of Mangaluru, south India.A Self-structured knowledge questionnaire was administered to the study participants.Results: The caregiver’s knowledge of the adverse effects of antipsychotics were assessed using descriptivestatistics. The results highlighted that more than half of the caregivers (67%) had inadequate knowledge ofthe adverse effects and management of antipsychotics, while 33% of them had adequate knowledge.